A method for preparing high temperature resistant and wear resistant polymer material

By forming an interpenetrating network cross-linking system under light conditions, the problem of degradation of material properties in the prior art is solved, high-temperature wear resistance and mechanical properties are improved, and self-lubricating and thermoplasticity.

CN117801275BActive Publication Date: 2024-12-31LILING JIEWEI SHOES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311834024.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2024-12-31
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

The prior art cannot effectively release the advantageous properties of both materials when combined with polyimide and polyether ether ketone resin, which leads to a decrease in a certain characteristic, and lacks polymer materials that can have high temperature wear resistance and mechanical properties at the same time. .

Method used

By placing the polyimide polymerization system and the polyether ether ketone polymerization system under the same polymerization system, a preliminary interpenetrating network cross-linking system is formed under light conditions, and condensation and reflux heating is carried out by toluene as a water-carrying agent to obtain resistant High temperature wear-resistant polymer material.

Benefits of technology

The high-temperature wear resistance and mechanical properties of the material have been improved, and the comprehensive properties of polyimide and polyether ether ketone are combined. The surface of the material has self-lubricity and good thermal plasticity, and the friction coefficient is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005006013300000101
    Figure GDA0005006013300000101
  • Figure GDA0005006013300000111
    Figure GDA0005006013300000111
  • Figure GDA0005006013300000112
    Figure GDA0005006013300000112
Patent Text Reader

Abstract

The invention discloses a preparation method of a novel high temperature resistant and wear resistant polymer material, and relates to the technical field of polymer materials. The invention places a polyimide polymerization system and a polyetheretherketone polymerization system in the same polymerization system, forms a preliminary interpenetrating network cross-linking system by synchronous copolymerization under light conditions, and then performs programmed temperature increase. By forming an interpenetrating network, the high temperature resistant and wear resistant polymer material can have the properties of both polyimide and polyetheretherketone. Both polyetheretherketone and polyimide have good mechanical properties and heat resistance. However, polyimide is prone to produce pores during the polycondensation process, which leads to a decrease in the performance of the synthesized material. However, the interpenetrating network can turn this disadvantage into an advantage. The pores produced by polyimide during the polycondensation process are just filled by polyetheretherketone, so that the synthesized material has good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a method for preparing a high temperature resistant and wear resistant polymer material. Background Art

[0002] Polyetheretherketone resin (PEEK) is a special engineering plastic with excellent performance. Compared with other engineering plastics, it has many advantages, such as high temperature resistance, excellent mechanical properties, good self-lubricating properties, chemical corrosion resistance, flame retardancy, peeling resistance, radiation resistance, stable insulation, hydrolysis resistance and easy processing. PEEK resin is a plastic that has both toughness and rigidity and achieves a balance. In particular, its excellent fatigue resistance to alternating stress is the most outstanding among all plastics and can be compared with alloys.

[0003] As a special engineering material, polyimide has been widely used in aviation, aerospace, microelectronics, nano, liquid crystal, separation membrane, laser and other fields. In the 1960s, all countries listed the research, development and utilization of polyimide as one of the most promising engineering plastics in the 21st century. Polyimide, due to its outstanding characteristics in performance and synthesis;

[0004] Conventionally, the two materials are combined by melt blending or block mixing. However, both methods cannot release the advantages of the two materials better. Instead, they often cause a sudden decrease in one of the properties of the material. Therefore, a polymer material that can possess the advantages of both materials is needed. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a high temperature resistant and wear resistant polymer material to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a high-temperature and wear-resistant polymer material. The high-temperature and wear-resistant polymer material is prepared by placing a polyimide polymerization system and a polyetheretherketone polymerization system in the same polymerization system, forming a preliminary interpenetrating network cross-linking system through synchronous copolymerization under light conditions, and using toluene as a water-carrying agent for condensation reflux heating to obtain the high-temperature and wear-resistant polymer material.

[0008] As an optimization, the following steps are included:

[0009] (1) Preparing a copolymerization mixed system: adding a photosensitive diamine monomer, biphenyltetracarboxylic acid dianhydride, a photosensitive diphenol monomer, 4,4'-difluorobenzophenone, anhydrous sodium sulfate and benzophenone to N-methylpyrrolidone in sequence, ultrasonically dispersing for 20 to 30 minutes, and vacuum stirring for 1 to 2 hours at a temperature of 5 to 10° C. to prepare a copolymerization mixed system;

[0010] (2) Preparation of a preliminary interpenetrating network crosslinking system: Place the copolymerization system in step (1) 10 to 15 cm below a 365 nm ultraviolet lamp with a light irradiance of 20 to 25 mW / cm 2 , standing for 1 to 2 hours, to obtain a preliminary interpenetrating network cross-linking system;

[0011] (3) Preparation of high temperature and wear resistant polymer materials: The preliminary interpenetrating network cross-linking system is stirred evenly and then sent into a condensation reflux reactor. Under nitrogen protection, the temperature of the condensation reflux reactor is controlled to be 120-135°C and the temperature of the condenser is 100-110°C. After reflux reaction for 2-3 hours, the temperature of the condensation reflux reactor is controlled to rise to 145-150°C and the reaction is carried out for 2-3 hours. The reaction is stopped and the preliminary interpenetrating network cross-linking system after the reaction is poured into deionized water with a mass of 10-15 times that of the preliminary interpenetrating network cross-linking system. After standing for 1-2 hours, it is filtered. The filter residue is washed with deionized water for 2-3 times. After washing, the filter residue is placed at a temperature of 100-120°C and vacuum dried for 10-12 hours to obtain a high temperature and wear resistant polymer material.

[0012] As an optimization, the photosensitive diamine monomer includes the following preparation steps: adding trifluoroacetic acid to dichloromethane with a mass of 1 to 1.2 times the mass of the trifluoroacetic acid, stirring evenly, and preparing a mixed solution; adding a photosensitive precursor to a mixed solution with a mass of 8 to 10 times the mass of the photosensitive precursor, stirring for a reaction of 1.5 to 2 hours at a temperature of 20 to 25° C., adding a saturated sodium bicarbonate solution with a mass of 10 to 12 times the mass of the trifluoroacetic acid, stirring evenly, standing and stratifying, collecting a lower organic layer, and removing the solvent by reduced pressure distillation at a temperature of 20 to 25° C. and a pressure of 120 to 140 Pa to obtain a photosensitive diamine monomer.

[0013] As an optimization, the photosensitive diphenol monomer includes the following preparation steps: placing a photosensitive precursor in a bubbling reactor, reacting for 15 to 30 minutes at a temperature of 170 to 180° C., after cooling to room temperature, adding 8 to 10 times the mass of dichloromethane of the photosensitive precursor, stirring evenly, standing for 1 to 2 hours, and filtering to obtain the photosensitive diphenol monomer.

[0014] As an optimization, the photosensitive precursor includes the following preparation steps: adding 2,2-bis(4-hydroxy-3-aminophenyl)propane to tetrahydrofuran with a mass of 20 to 25 times that of 2,2-bis(4-hydroxy-3-aminophenyl)propane, stirring evenly at a temperature of 0 to 5°C, adding trifluoroacetic anhydride with a mass of 1.5 to 2 times that of 2,2-bis(4-hydroxy-3-aminophenyl)propane, stirring at a temperature of 0 to 5°C for 1 to 1.5 hours, heating to 20 to 25°C and stirring for 1 to 1.5 hours, and then removing the solvent by reduced pressure distillation at a temperature of 30 to 35°C and a pressure of 120 to 140 Pa to obtain a precursor; adding 2-chlorothioxanthone to The method comprises the following steps: adding the precursor to anhydrous acetone in an amount of 10 to 15 times the mass of 2-chlorothioxanthone, stirring evenly, and preparing a 2-chlorothioxanthone solution; adding the precursor to anhydrous acetone in an amount of 10 to 15 times the mass of the precursor, stirring evenly, and preparing a precursor solution; at a temperature of 0 to 5° C., uniformly dropping the 2-chlorothioxanthone solution into the precursor solution within 1.5 to 2 hours, stirring evenly, and standing for 0.5 to 1 hour at a temperature of 20 to 25° C. under argon protection, and then heating to 40 to 45° C., reacting for 10 to 12 hours, and then removing the solvent by reduced pressure distillation at a temperature of 30 to 35° C. and a pressure of 120 to 140 Pa to obtain a photosensitive precursor.

[0015] As an optimization, the molar ratio between the photosensitive diamine monomer and biphenyltetracarboxylic dianhydride is 1:4-6.

[0016] As an optimization, the molar ratio between the photosensitive diphenol monomer and 4,4'-difluorobenzophenone is 1:10-15.

[0017] As an optimization, the mass ratio of the biphenyltetracarboxylic dianhydride, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, benzophenone, nano titanium dioxide, toluene and N-methylpyrrolidone is 1:2-4:3:0.2-0.5:0.3-0.5:5:10-15.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention prepares a high temperature and wear resistant polymer material by placing a polyimide polymerization system and a polyetheretherketone polymerization system in the same polymerization system, forming a preliminary interpenetrating network cross-linking system through synchronous copolymerization under light conditions, and then performing thermal curing.

[0020] First, 2,2-bis(4-hydroxy-3-aminophenyl)propane is connected to trifluoroacetic anhydride for amino protection, and then a photosensitive group thioxanthone is connected to prepare a photosensitive precursor. The photosensitive precursor is converted into a photosensitive diamine monomer by removing the trifluoroacetyl group on the amino group. The photosensitive precursor first removes the trifluoroacetyl group at high temperature and then transfers the trifluoroacetyl group on the hydroxyl group to the amino group through ester exchange to convert it into a photosensitive diphenol monomer. A polyimide polymerization system is constructed with the photosensitive diamine monomer, 2,6-diaminotoluene and biphenyltetracarboxylic acid dianhydride, and a polyetheretherketone polymerization system is constructed with photosensitive diphenol and 4,4-dihydroxybiphenyl. Benzophenone is used as a photoinitiator to initiate copolymerization under light conditions, and anhydrous sodium sulfate is added as a water absorbent to form a preliminary interpenetrating network cross-linking system, and then thermal curing is performed to firmly anchor titanium dioxide in the system through the interpenetrating network, thereby improving the wear resistance of the material.

[0021] During the thermal curing process of the preliminary interpenetrating network cross-linking system, toluene is used as a water-carrying agent to carry out condensation reflux reaction to remove water from the reaction system, thereby reducing the occurrence of side reactions in the reaction; by forming an interpenetrating network, the high temperature and wear-resistant polymer material can have the properties of both polyimide and polyetheretherketone. Both polyetheretherketone and polyimide have good mechanical properties and heat resistance. However, polyimide is prone to produce pores during the polycondensation process, which leads to a decrease in the performance of the synthesized material. However, the interpenetrating network can turn this disadvantage into an advantage. The pores produced by polyimide during the polycondensation process are just filled by polyetheretherketone, so that the synthesized material has good mechanical properties. In addition, the interpenetrating network prepared by the copolymerization method has a more uniform distribution of the two, so that the surface of the material has the self-lubricating property of polyetheretherketone, which makes it have a lower friction resistance coefficient, but polyetheretherketone has poor thermoplasticity. By forming an interpenetrating network structure between polyimide and polyetheretherketone, it has a certain plasticity of polyimide, so that the material has good thermoplasticity. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] A method for preparing a high-temperature and wear-resistant polymer material. The high-temperature and wear-resistant polymer material is prepared by placing a polyimide polymerization system and a polyetheretherketone polymerization system in the same polymerization system, forming a preliminary interpenetrating network cross-linking system through synchronous copolymerization under light conditions, and using toluene as a water-carrying agent for condensation reflux heating to obtain the high-temperature and wear-resistant polymer material.

[0025] A method for preparing a high temperature resistant and wear resistant polymer material comprises the following steps:

[0026] (1) Preparation of a photosensitive precursor: 2,2-bis(4-hydroxy-3-aminophenyl)propane was added to tetrahydrofuran (20 times the mass of 2,2-bis(4-hydroxy-3-aminophenyl)propane), and the mixture was stirred at 0°C. Trifluoroacetic anhydride (1.5 times the mass of 2,2-bis(4-hydroxy-3-aminophenyl)propane) was added, and the mixture was stirred at 0°C for 1 h. After the mixture was heated to 20°C and stirred for 1 h, the solvent was removed by reduced pressure distillation at 30°C and 120 Pa to obtain a precursor. 2-Chlorothioxanthone was added to 2-chlorothioxanthone. The precursor was added to anhydrous acetone with a mass of 10 times that of the precursor, and stirred evenly to prepare a 2-chlorothioxanthone solution; the precursor was added to anhydrous acetone with a mass of 10 times that of the precursor, and stirred evenly to prepare a precursor solution; at a temperature of 0°C, the 2-chlorothioxanthone solution was evenly added dropwise to the precursor solution within 1.5 hours, and stirred evenly, and under argon protection, the temperature was 20°C, and the mixture was allowed to stand for 0.5 hours, and then the temperature was raised to 40°C. After reacting for 10 hours, the solvent was removed by reduced pressure distillation at a temperature of 30°C and a pressure of 120Pa to obtain a photosensitive precursor;

[0027] (2) Preparing a photosensitive diamine monomer: adding trifluoroacetic acid to dichloromethane with a mass of 1 times that of the trifluoroacetic acid, stirring evenly to prepare a mixed solution; adding a photosensitive precursor to a mixed solution with a mass of 8 times that of the photosensitive precursor, stirring for 1.5 hours at a temperature of 20° C., adding a saturated sodium bicarbonate solution with a mass of 10 times that of the trifluoroacetic acid, stirring evenly, standing and stratifying, collecting the lower organic layer, and removing the solvent by reduced pressure distillation at a temperature of 20° C. and a pressure of 120 Pa to obtain a photosensitive diamine monomer;

[0028] (3) Preparation of photosensitive diphenol monomer: placing the photosensitive precursor in a bubbling reactor, reacting at 170° C. for 15 min, and after cooling to room temperature, adding dichloromethane 8 times the mass of the photosensitive precursor, stirring evenly, standing for 1 h, and filtering to obtain the photosensitive diphenol monomer;

[0029] (4) Preparing a copolymerization mixed system: adding a photosensitive diamine monomer, biphenyltetracarboxylic acid anhydride, a photosensitive diphenol monomer, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, nano-titanium dioxide, toluene and benzophenone to N-methylpyrrolidone in sequence, wherein the molar ratio of the photosensitive diamine monomer to the biphenyltetracarboxylic acid anhydride is 1:4, the molar ratio of the photosensitive diphenol monomer to the 4,4'-difluorobenzophenone is 1:10, and the mass ratio of the biphenyltetracarboxylic acid anhydride, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, benzophenone, nano-titanium dioxide, toluene and N-methylpyrrolidone is 1:2:3:0.2:0.3:5:10, performing ultrasonic dispersion for 20 minutes, and stirring under vacuum at a temperature of 5°C for 1 hour to prepare a copolymerization mixed system;

[0030] (5) Preparation of a preliminary interpenetrating network cross-linking system: The copolymerization system in step (4) was placed 10 cm below a 365 nm ultraviolet lamp with a light irradiance of 20 mW / cm 2 , let stand for 1h to obtain a preliminary interpenetrating network cross-linking system;

[0031] (6) Preparation of high temperature and wear resistant polymer materials: The preliminary interpenetrating network cross-linking system is stirred evenly and then sent into a condensation reflux reactor. Under nitrogen protection, the temperature of the condensation reflux reactor is controlled to be 120°C and the condenser temperature is 100°C. After reflux reaction for 2 hours, the temperature of the condensation reflux reactor is controlled to rise to 145°C and the reaction is carried out for 2 hours. The reaction is stopped and the preliminary interpenetrating network cross-linking system after the reaction is poured into deionized water with a mass 10 times that of the preliminary interpenetrating network cross-linking system. After standing for 1 hour, it is filtered. The filter residue is washed twice with deionized water. After washing, the filter residue is placed at a temperature of 100°C and vacuum dried for 10 hours to obtain a high temperature and wear resistant polymer material.

[0032] Example 2

[0033] A method for preparing a high temperature resistant and wear resistant polymer material comprises the following steps:

[0034] (1) Preparation of a photosensitive precursor: 2,2-bis(4-hydroxy-3-aminophenyl)propane was added to tetrahydrofuran (22 times the mass of 2,2-bis(4-hydroxy-3-aminophenyl)propane), and the mixture was stirred at 3°C. Trifluoroacetic anhydride (1.7 times the mass of 2,2-bis(4-hydroxy-3-aminophenyl)propane) was added, and the mixture was stirred at 3°C ​​for 1 h. After the mixture was heated to 22°C and stirred for 1.2 h, the solvent was removed by reduced pressure distillation at 32°C and 130 Pa to obtain a precursor. 2-Chlorothioxanthone was added to 2-chlorothioxanthone. The precursor was added to anhydrous acetone with a mass of 12 times that of the precursor, and stirred evenly to prepare a 2-chlorothioxanthone solution; the precursor was added to anhydrous acetone with a mass of 12 times that of the precursor, and stirred evenly to prepare a precursor solution; at a temperature of 3°C, the 2-chlorothioxanthone solution was evenly added dropwise to the precursor solution within 1.5 hours, and stirred evenly. Under argon protection, the temperature was 22°C, and the mixture was allowed to stand for 0.6 hours, then heated to 42°C, reacted for 11 hours, and then the solvent was removed by reduced pressure distillation at a temperature of 32°C and a pressure of 130Pa to obtain a photosensitive precursor;

[0035] (2) Preparing a photosensitive diamine monomer: adding trifluoroacetic acid to dichloromethane with a mass of 1.1 times that of the trifluoroacetic acid, stirring evenly, and preparing a mixed solution; adding a photosensitive precursor to a mixed solution with a mass of 9 times that of the photosensitive precursor, stirring for 1.8 hours at a temperature of 22° C., adding a saturated sodium bicarbonate solution with a mass of 11 times that of the trifluoroacetic acid, stirring evenly, standing and stratifying, collecting the lower organic layer, and removing the solvent by reduced pressure distillation at a temperature of 22° C. and a pressure of 130 Pa to obtain a photosensitive diamine monomer;

[0036] (3) Preparation of photosensitive diphenol monomer: placing the photosensitive precursor in a bubbling reactor, reacting at 175° C. for 20 min, and after cooling to room temperature, adding dichloromethane 9 times the mass of the photosensitive precursor, stirring evenly, standing for 1.5 h, and filtering to obtain the photosensitive diphenol monomer;

[0037] (4) Preparing a copolymerization mixed system: adding a photosensitive diamine monomer, biphenyltetracarboxylic acid anhydride, a photosensitive diphenol monomer, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, nano-titanium dioxide, toluene and benzophenone to N-methylpyrrolidone in sequence, wherein the molar ratio of the photosensitive diamine monomer to biphenyltetracarboxylic acid anhydride is 1:4, the molar ratio of the photosensitive diphenol monomer to 4,4'-difluorobenzophenone is 1:10, and the mass ratio of the biphenyltetracarboxylic acid anhydride, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, benzophenone, nano-titanium dioxide, toluene and N-methylpyrrolidone is 1:3:3:0.4:0.4:5:12, performing ultrasonic dispersion for 20 minutes, and stirring under vacuum at a temperature of 5°C for 1 hour to prepare a copolymerization mixed system;

[0038] (5) Preparation of a preliminary interpenetrating network cross-linking system: The copolymerization system in step (4) was placed 10 cm below a 365 nm ultraviolet lamp with a light irradiance of 20 mW / cm 2 , let stand for 1h to obtain a preliminary interpenetrating network cross-linking system;

[0039] (6) Preparation of high temperature and wear resistant polymer materials: The preliminary interpenetrating network cross-linking system is stirred evenly and then sent into a condensation reflux reactor. Under nitrogen protection, the temperature of the condensation reflux reactor is controlled to be 120°C and the condenser temperature is 100°C. After reflux reaction for 2 hours, the temperature of the condensation reflux reactor is controlled to rise to 145°C and the reaction is carried out for 2 hours. The reaction is stopped and the preliminary interpenetrating network cross-linking system after the reaction is poured into deionized water with a mass 10 times that of the preliminary interpenetrating network cross-linking system. After standing for 1 hour, it is filtered. The filter residue is washed twice with deionized water. After washing, the filter residue is placed at a temperature of 100°C and vacuum dried for 10 hours to obtain a high temperature and wear resistant polymer material.

[0040] Example 3

[0041] A method for preparing a high temperature resistant and wear resistant polymer material comprises the following steps:

[0042] (1) Preparation of a photosensitive precursor: 2,2-bis(4-hydroxy-3-aminophenyl)propane was added to tetrahydrofuran (25 times the mass of 2,2-bis(4-hydroxy-3-aminophenyl)propane), and the mixture was stirred at 5°C. Trifluoroacetic anhydride (2 times the mass of 2,2-bis(4-hydroxy-3-aminophenyl)propane) was added, and the mixture was stirred at 5°C for 1.5 h. After the mixture was heated to 25°C and stirred for 1.5 h, the solvent was removed by reduced pressure distillation at 35°C and 140 Pa to obtain a precursor. 2-Chlorothioxanthone was added to 2 -chlorothioxanthone in anhydrous acetone with a mass of 15 times, stirring evenly to prepare a 2-chlorothioxanthone solution; adding the precursor to anhydrous acetone with a mass of 15 times the mass of the precursor, stirring evenly, and preparing a precursor solution; at a temperature of 5°C, the 2-chlorothioxanthone solution is evenly added dropwise to the precursor solution within 2 hours, stirring evenly, under argon protection, the temperature is 25°C, standing for 1 hour, then heating to 45°C, reacting for 12 hours, and under a temperature of 35°C and a pressure of 140Pa, the solvent is removed by reduced pressure distillation to obtain a photosensitive precursor;

[0043] (2) Preparing a photosensitive diamine monomer: adding trifluoroacetic acid to dichloromethane with a mass of 1.2 times that of the trifluoroacetic acid, stirring evenly, and preparing a mixed solution; adding a photosensitive precursor to a mixed solution with a mass of 10 times that of the photosensitive precursor, stirring for 2 hours at a temperature of 25° C., adding a saturated sodium bicarbonate solution with a mass of 12 times that of the trifluoroacetic acid, stirring evenly, standing and stratifying, collecting the lower organic layer, and removing the solvent by reduced pressure distillation at a temperature of 25° C. and a pressure of 140 Pa to obtain a photosensitive diamine monomer;

[0044] (3) Preparation of photosensitive diphenol monomer: placing a photosensitive precursor in a bubbling reactor, reacting at 180° C. for 30 min, and after cooling to room temperature, adding dichloromethane 10 times the mass of the photosensitive precursor, stirring evenly, standing for 2 h, and filtering to obtain a photosensitive diphenol monomer;

[0045] (4) Preparing a copolymerization mixed system: adding a photosensitive diamine monomer, biphenyltetracarboxylic acid anhydride, a photosensitive diphenol monomer, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, nano-titanium dioxide, toluene and benzophenone to N-methylpyrrolidone in sequence, wherein the molar ratio of the photosensitive diamine monomer to biphenyltetracarboxylic acid anhydride is 1:4, the molar ratio of the photosensitive diphenol monomer to 4,4'-difluorobenzophenone is 1:10, and the mass ratio of the biphenyltetracarboxylic acid anhydride, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, benzophenone, nano-titanium dioxide, toluene and N-methylpyrrolidone is 1:4:3:0.5:0.5:5:15, performing ultrasonic dispersion for 20 minutes, and stirring under vacuum at a temperature of 5°C for 1 hour to prepare a copolymerization mixed system;

[0046] (5) Preparation of a preliminary interpenetrating network cross-linking system: The copolymerization system in step (4) was placed 10 cm below a 365 nm ultraviolet lamp with a light irradiance of 20 mW / cm 2 , let stand for 1h to obtain a preliminary interpenetrating network cross-linking system;

[0047] (6) Preparation of high temperature and wear resistant polymer materials: The preliminary interpenetrating network cross-linking system is stirred evenly and then sent into a condensation reflux reactor. Under nitrogen protection, the temperature of the condensation reflux reactor is controlled to be 120°C and the condenser temperature is 100°C. After reflux reaction for 2 hours, the temperature of the condensation reflux reactor is controlled to rise to 145°C and the reaction is carried out for 2 hours. The reaction is stopped and the preliminary interpenetrating network cross-linking system after the reaction is poured into deionized water with a mass 10 times that of the preliminary interpenetrating network cross-linking system. After standing for 1 hour, it is filtered. The filter residue is washed twice with deionized water. After washing, the filter residue is placed at a temperature of 100°C and vacuum dried for 10 hours to obtain a high temperature and wear resistant polymer material.

[0048] Comparative Example 1

[0049] The difference between the preparation method of the high temperature resistant and wear resistant polymer material of Comparative Example 1 and Example 2 is that nano titanium dioxide is not added in step (4).

[0050] Comparative Example 2

[0051] The difference between the preparation method of the high temperature resistant and wear resistant polymer material of Comparative Example 2 and Example 2 is that the step (4) of "adding photosensitive diamine monomer, biphenyltetracarboxylic acid dianhydride, photosensitive diphenol monomer, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, nano titanium dioxide, toluene and benzophenone to N-methylpyrrolidone in sequence" is modified to "adding photosensitive diphenol monomer, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, nano titanium dioxide, toluene and benzophenone to N-methylpyrrolidone in sequence".

[0052] Comparative Example 3

[0053] The difference between the preparation method of the high temperature resistant and wear resistant polymer material of Comparative Example 3 and Example 2 is that the step (4) of "adding photosensitive diamine monomer, biphenyltetracarboxylic acid dianhydride, photosensitive diphenol monomer, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, nano titanium dioxide, toluene and benzophenone to N-methylpyrrolidone in sequence" is modified to "adding photosensitive diamine monomer, biphenyltetracarboxylic acid dianhydride, anhydrous sodium sulfate, nano titanium dioxide, toluene and benzophenone to N-methylpyrrolidone in sequence".

[0054] Comparative Example 4

[0055] The high temperature resistant and wear resistant polymer materials prepared in Comparative Example 2 and Comparative Example 3 were mixed at a mass ratio of 40:60 of Comparative Example 2: Comparative Example 3, and after mixing, added into a high-speed mixer for premixing to obtain a high temperature resistant and wear resistant polymer material.

[0056] Comparative Example 5

[0057] The high temperature resistant and wear resistant polymer materials prepared in Comparative Example 2 and Comparative Example 3 were mixed in a mass ratio of 50:50, and after mixing, added into a high-speed mixer for premixing to obtain a high temperature resistant and wear resistant polymer material.

[0058] Comparative Example 6

[0059] The high temperature resistant and wear resistant polymer materials prepared in Comparative Example 2 and Comparative Example 3 were mixed at a mass ratio of 60:40 of Comparative Example 2: Comparative Example 3, and after mixing, added into a high-speed mixer for premixing to obtain a high temperature resistant and wear resistant polymer material.

[0060] Test Example 1

[0061] Preparation of samples: The high temperature and wear resistant polymer materials obtained in Example 2 and Comparative Examples 1 to 6 were melt blended by a twin-screw extruder. The temperatures of each section of the barrel were 280 / 350 / 355 / 360 / 360 / 355°C and the twin-screw speed was set to 80r / min. After extrusion granulation, the samples were injection molded by an injection molding machine to form strips.

[0062] Tensile properties test

[0063] The test instrument is an EH-5000 universal testing machine. The tensile speed is set to 5 mm / min at room temperature until it breaks. The test result is the average value of 5 measurement data.

[0064] Test standard: tensile performance test according to GB / T1040-2006 standard;

[0065] The test specimen is a dumbbell-shaped standard specimen with dimensions of 75 mm × 12 mm × 2 mm;

[0066] Bending performance test

[0067] The test instrument is an EH-5000 universal testing machine. The tensile speed is set to 2 mm / min at room temperature until it breaks. The test result is the average value of 5 measurement data.

[0068] Test standard: GB / T9341-2000 standard for bending performance test;

[0069] The test specimen is a rectangular parallelepiped with dimensions of 75 mm × 12 mm × 4 mm;

[0070] Table 1 - Mechanical properties test data

[0071]

[0072]

[0073] From the comparison of the experimental data of Example 2 and Comparative Examples 1 to 6 in Table 1, it can be found that the high temperature resistant and wear resistant polymer material prepared by the present invention has good mechanical properties.

[0074] By comparison, Example 2 has better mechanical properties than Comparative Examples 2 and 3. It can be found that the mechanical properties of the high-temperature and wear-resistant polymer material with an interpenetrating cross-linked network are better than those of polyimide and polyetheretherketone monomer polymers. This is because the formation of an interpenetrating cross-linked network will make the two polymers more tightly bonded, and the simultaneous blending will make their distribution more uniform. Therefore, the obtained high-temperature and wear-resistant polymer material has higher performance than its monomer polymer.

[0075] By comparison, Example 2 has better mechanical properties than Comparative Examples 4, 5 and 6, which shows that although the mechanical properties of simple melt blending are partially improved, they are still lower than those of the high-temperature and wear-resistant polymer materials with an interpenetrating cross-linked network, because simple blending cannot form more cross-linked networks between the two polymers, and the improvement of its mechanical properties is not very obvious.

[0076] Test Example 2

[0077] Preparation of samples: The high temperature and wear resistant polymer materials prepared in Example 2 and Comparative Examples 1 to 6 were melt blended by a twin-screw extruder. The temperatures of each section of the barrel were 280 / 350 / 355 / 360 / 360 / 355°C, the twin-screw speed was set to 80 r / min, and extrusion granulation was performed.

[0078] Thermal gravimetric test

[0079] The test instrument is a TGA-2050 thermogravimetric analyzer; in an air atmosphere, the heating rate is 10°C / min, the test temperature range is 100-850°C, the gas flow rate is 200mL / min, and the sample mass is 10mg.

[0080] Table 2 - Thermal Weight Loss Test Data

[0081]

[0082]

[0083] From the comparison of the experimental data of Example 2 and Comparative Examples 1 to 6 in Table 2, it can be found that the high temperature and wear resistant polymer material having an interpenetrating cross-linked network has a T d10 All of them are relatively stable, among which the initial thermal weight loss temperatures of the high temperature resistant and wear resistant polymer materials of Example 2 and Comparative Examples 1 to 6 are substantially higher than or equal to those of other materials, indicating that the composite materials have excellent thermal stability.

[0084] Test Example 3

[0085] Friction and wear performance test

[0086] Preparation of samples: The high temperature and wear resistant polymer materials obtained in Example 2 and Comparative Examples 1 to 6 were melt blended by a twin-screw extruder. The temperatures of each section of the barrel were 280 / 350 / 355 / 360 / 360 / 355°C and the twin-screw speed was set to 80r / min. After extrusion granulation, the samples were injection molded by an injection molding machine to form strips.

[0087] The testing instrument is UMT-2 friction testing machine;

[0088] Test standard: The friction and wear performance of the samples were tested according to ASTMG99-04 standard. The contact type of the friction pair is surface loading, where the standard sample is a cylindrical pin with a size of φ6.3mm×18.8mm, the contact form is point / co-curved surface, and the metal friction pair disc is 45# stainless steel with a size of φ50mm×10mm. The friction loading form is divided into static load and dynamic load, and its movement form is unidirectional sliding and vibration. Before the test, the sample surface needs to be pre-grinded with 500# and 1000# sandpaper. The test load Fz=31.16N, and the sample slides on the disc for 2h at 200r / min and a rotation radius of 20mm.

[0089] Table 3-Friction and wear performance test data

[0090]

[0091] From the comparison of the experimental data of Example 2 and Comparative Examples 1 to 6 in Table 2, it can be found that the high temperature resistant and wear resistant polymer material with an interpenetrating cross-linked network has a smaller friction coefficient and wear rate, mainly because the window protection cross-linked network makes the combination between polyimide and polyetheretherketone tighter, but it is higher than that of Comparative Example 5 mainly because it contains more nano titanium dioxide powder, thereby improving its wear resistance.

[0092] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a high temperature resistant and wear resistant polymer material, characterized in that: The high temperature and wear resistant polymer material is prepared by placing a polyimide polymerization system and a polyetheretherketone polymerization system in the same polymerization system, forming a preliminary interpenetrating network cross-linking system through synchronous copolymerization under light conditions, and using toluene as a water-carrying agent for condensation reflux heating to obtain the high temperature and wear resistant polymer material; The method for preparing the high temperature resistant and wear resistant polymer material comprises the following steps: (1) Preparation of a copolymerization mixed system: Add photosensitive diamine monomer, biphenyltetracarboxylic acid dianhydride, photosensitive diphenol monomer, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, nano-titanium dioxide, toluene and benzophenone to N-methylpyrrolidone in sequence, ultrasonically disperse for 20-30 minutes, and vacuum stir for 1-2 hours at a temperature of 5-10°C to obtain a copolymerization mixed system; (2) Preparation of preliminary interpenetrating network cross-linking system: Place the copolymerization system in step (1) 10-15 cm below a 365 nm ultraviolet lamp with a light irradiance of 20-25 mW / cm 2 , let it stand for 1-2 hours to obtain a preliminary interpenetrating network cross-linking system; (3) Preparation of high temperature and wear resistant polymer materials: The preliminary interpenetrating network cross-linking system is stirred evenly and then sent into a condensation reflux reactor. Under nitrogen protection, the temperature of the condensation reflux reactor is controlled to be 120-135°C and the condenser temperature is 100-110°C. After reflux reaction for 2-3 hours, the temperature of the condensation reflux reactor is controlled to rise to 145-150°C and the reaction is carried out for 2-3 hours. The reaction is stopped and the preliminary interpenetrating network cross-linking system after the reaction is poured into deionized water with a mass of 10-15 times that of the preliminary interpenetrating network cross-linking system. After standing for 1-2 hours, the filter is filtered and the filter residue is washed with deionized water for 2-3 times. After washing, the filter residue is placed at a temperature of 100-120°C and vacuum dried for 10-12 hours to obtain a high temperature and wear resistant polymer material. The photosensitive diamine monomer comprises the following preparation steps: adding trifluoroacetic acid to dichloromethane with a mass of 1 to 1.2 times the mass of the trifluoroacetic acid, stirring evenly, and preparing a mixed solution; adding a photosensitive precursor to the mixed solution with a mass of 8 to 10 times the mass of the photosensitive precursor, stirring for reaction for 1.5 to 2 hours at a temperature of 20 to 25° C., adding a saturated sodium bicarbonate solution with a mass of 10 to 12 times the mass of the trifluoroacetic acid, stirring evenly, standing for stratification, collecting a lower organic layer, and removing the solvent by reduced pressure distillation at a temperature of 20 to 25° C. and a pressure of 120 to 140 Pa to obtain a photosensitive diamine monomer; The photosensitive diphenol monomer comprises the following preparation steps: placing a photosensitive precursor in a bubbling reaction kettle, reacting for 15 to 30 minutes at a temperature of 170 to 180° C., adding dichloromethane in an amount of 8 to 10 times the mass of the photosensitive precursor after cooling to room temperature, stirring evenly, standing for 1 to 2 hours, and filtering to obtain the photosensitive diphenol monomer; The photosensitive precursor comprises the following preparation steps: adding 2,2-bis(4-hydroxy-3-aminophenyl)propane to tetrahydrofuran (20 to 25 times the mass of 2,2-bis(4-hydroxy-3-aminophenyl)propane), stirring evenly at a temperature of 0 to 5°C, adding trifluoroacetic anhydride (1.5 to 2 times the mass of 2,2-bis(4-hydroxy-3-aminophenyl)propane), stirring at a temperature of 0 to 5°C for 1 to 1.5 hours, heating to 20 to 25°C and stirring for 1 to 1.5 hours, and then removing the solvent by reduced pressure distillation at a temperature of 30 to 35°C and a pressure of 120 to 140 Pa to obtain a precursor; adding 2-chlorothioxanthone to 2- The chlorothioxanthone is added to anhydrous acetone with a mass of 10 to 15 times, and stirred evenly to prepare a 2-chlorothioxanthone solution; the precursor is added to anhydrous acetone with a mass of 10 to 15 times the mass of the precursor, and stirred evenly to prepare a precursor solution; at a temperature of 0 to 5°C, the 2-chlorothioxanthone solution is evenly added dropwise to the precursor solution within 1.5 to 2 hours, and stirred evenly, under argon protection conditions, the temperature is 20 to 25°C, and the mixture is allowed to stand for 0.5 to 1 hour, then the temperature is raised to 40 to 45°C, and after reacting for 10 to 12 hours, the solvent is removed by reduced pressure distillation at a temperature of 30 to 35°C and a pressure of 120 to 140Pa to obtain a photosensitive precursor; The molar ratio between the photosensitive diamine monomer and biphenyltetracarboxylic dianhydride is 1:4-6; The molar ratio between the photosensitive diphenol monomer and 4,4'-difluorobenzophenone is 1:10-15; The mass ratio of the biphenyltetracarboxylic acid dianhydride, 4,4'-difluorobenzophenone, anhydrous sodium sulfate, benzophenone, nano titanium dioxide, toluene and N-methylpyrrolidone is 1:2-4:3:0.2-0.5:0.3-0.5:5:10-15.